First acanthodian from the Upper Devonian (Frasnian) Gogo Formation, Western Australia - Burrow, C.; Trinajstic, Kate; Long, J. (Taylor & Francis, 2012)
A new acanthodiform acanthodian Halimacanthodes ahlbergi n. gen. n. sp., based on a single uncrushed, partial articulated specimen, represents the first acanthodian collected from the Gogo Formation, Canning Basin, Western Australia. The delicate perichondral ossifications of the lower jaws, branchial skeleton and endoskeletal shoulder girdle are preserved in 3D. H. ahlbergi n. gen. n. sp. is characterised by having a tall slender scapular shaft, paired pelvic fin spines, mineralised branchial arches and scales with an anterior median depression and a microornament of tiny smooth tubercles randomly distributed on the crown. In having paired pelvic spines and lacking prepelvic spines, it is most closely related to Howittacanthus kentoni from Frasnian lacustrine deposits of eastern Victoria. Isolated scales, here attributed to the new taxon, are found in the coeval Gneudna Formation, Carnarvon Basin, Western Australia.